STRESS ANALYSIS OF VARIOUS DESIGNS OF CENTRIFUGAL PUMP IMPELLERS USING FINITE ELEMENT METHOD - Mohamed, Nuradin; Dr Chong Perk Lin; Faraji, Foad; Moey, Lip Kean; Ibrahim, Abdulwehab; Yazdi, Mohammad Hossein; Merdji, Ali (Journal of Engineering & Technological Advances, 2022)
The impeller blade is among the many critical components in a centrifugal pump that affect the efficiency of the pump, as it is the component through which the fluid passes. Therefore, the impeller requires as many analysis as possible to maximise its efficiency. The main requirement is to ensure that the impeller blade can withstand the level of stress thereby reducing the chance of blade fracture. In this paper, 4 different designs of a centrifugal pump impeller were analysed and compared using finite element analysis (FEA) under static analysis. The geometry of centrifugal pump impellers was modelled and analysed using Siemens NX™ software. This analysis provided an insight of performance of design where the blade’s angle, width and shrouds are kept constant throughout the process. Calculations were performed to predict the design discharge and understand the impact on the impeller if the blade angle changes. The analysis revealed that the higher the outlet blade angle is to a point in comparison to the blade at inlet, the higher the head and the higher the pressure at the outlet will be. A pressure load of 1.866 MPa was applied evenly to the impellers with a rotation of 1,100 rpm and a torque of 29.187 Nm. Throughout the analysis, closed impeller blades were set to produce the least stress and displacement in comparison to other designs. Therefore, closed impeller was the best design, where the maximum stress was the lowest (86.09MPa) and can be more reliable in real life application.